2022
DOI: 10.1037/xge0001154
|View full text |Cite
|
Sign up to set email alerts
|

Self-referential processing accounts for cultural variation in self-enhancement versus criticism: An electrocortical investigation.

Abstract: European Americans are self-enhancing, whereas East Asians are sometimes self-critical. However, the mechanisms underlying this cultural difference remain unclear. Here, we addressed this gap by testing 32 Taiwanese and 32 American young adults, who indicated whether their self-esteem would change in various episodes involving success or failure. We monitored their electroencephalogram (EEG) and assessed upperalpha band power in response to the outcome information. An increase in upper-alpha power indicates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 62 publications
4
15
1
Order By: Relevance
“…Hence, the propensity of European Americans to express disengaging emotions, especially positive emotions such as pride, might be more pronounced than their expression of negative socially disengaging emotions like anger. This effect is likely to be observed primarily in situations that allow for self-enhancement, such as instances where individuals experience personal success rather than failure (Kitayama et al, 1997; Salvador et al, 2022).…”
Section: Interdependent Orientation In Latin Americamentioning
confidence: 99%
“…Hence, the propensity of European Americans to express disengaging emotions, especially positive emotions such as pride, might be more pronounced than their expression of negative socially disengaging emotions like anger. This effect is likely to be observed primarily in situations that allow for self-enhancement, such as instances where individuals experience personal success rather than failure (Kitayama et al, 1997; Salvador et al, 2022).…”
Section: Interdependent Orientation In Latin Americamentioning
confidence: 99%
“…In addition, future work should incorporate neural measures, as previous research has indicated that these may be more sensitive markers of the in uence of culture than behavioral measures [42]. Previous work using ERP and fMRI has demonstrated that cultural groups differ in the neural response to self versus close others [39,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The positive link between harmony seeking and rumination in the Japanese sample fits with past research, suggesting that Japanese may engage in self‐critical thinking to promote social adjustment and maintain harmonious relationships (Heine et al., 1999; Schunk et al., 2021). In contrast, focusing on negative information about the self is presumed to be less desirable in a Western cultural context due to social norms that promote self‐enhancement (Heine et al., 1999; Salvador et al., 2021). The negative link between harmony seeking and rumination for HKC would be in line with this Western interpretation.…”
Section: Discussionmentioning
confidence: 99%